Radiative decay of the ^{229m}Th nuclear clock isomer in different host materials - S. V. Pineda; P. Chhetri; S. Bara; Y. Elskens; S. Casci; A. N. Alexandrova; M. Au; M. Athanasakis-Kaklamanakis; M. Bartokos; K. Beeks; C. Bernerd; A. Claessens; et al. (Physical Review Research)
A comparative vacuum ultraviolet spectroscopy study conducted at ISOLDE-CERN of the radiative decay of the ^{229m}Th nuclear clock isomer embedded in different host materials is reported. The ratio of the number of radiative decay photons and the number of ^{229m}Th embedded are determined for single crystalline CaF_{2}, MgF_{2}, LiSrAlF_{6}, AlN, and amorphous SiO_{2}. For the latter two materials, no radiative decay signal was observed and an upper limit of the ratio is reported. The radiative decay wavelength was determined in LiSrAlF_{6} and CaF_{2}, reducing its uncertainty by a factor of 2.5 relative to our previous measurement. This value is in agreement with the recently reported improved values from laser excitation.